The Pilotage Policy Paradox: Competency Gaps and Maritime Education Reform in Indonesia - Anggita Aryati; Marihot Simanjuntak; Irfan Faozun (Yayasan Pendidikan Penelitian Pengabdian Algero, 2026)
Indonesia's policy delegating pilotage services to Port Business Entities (BUPs) aims to enhance efficiency and Non-Tax State Revenue (PNBP). While quantitative Key Performance Indicators (KPIs) at six BUPs show